I Keep Counting: An Experiment in Human/AI Co-creative Songwriting. Issue 1 (21st December 2021) - Micchi, Gianluca; Bigo, Louis; Giraud, Mathieu; Groult, Richard; Levé, Florence
Musical co-creativity aims at making humans and computers collaborate to compose music. As an MIR team in computational musicology, we experimented with co-creativity when writing our entry to the "AI Song Contest 2020". Artificial intelligence was used to generate the song's structure, harmony, lyrics, and hook melody independently and as a basis for human composition. It was a challenge from both the creative and the technical point of view: in a very short time-frame, the team had to adapt its own simple models, or experiment with existing ones, to a related yet still unfamiliar task, music generation through AI. The song we propose is called "I Keep Counting". We openly detail the process of songwriting, arrangement, and production. This experience raised many questions on the relationship between creativity and machine, both in music analysis and generation, and on the role AI could play to assist a composer in their work. We experimented with AI as automation, mechanizing some parts of the composition, and especially AI as suggestion to foster the composer's creativity, thanks to surprising lyrics, uncommon successions of sections and unexpected chord progressions. Working with this material was thus a stimulus for human creativity.